IDIOM’S TRANSLATION PROCEDURES FROM INDONESIAN INTO GERMAN - Ary Fadjar Isdiati (EEAL Journal (English Education and Applied Linguistics Journal), 2019)
When the translator translate idioms from source language into target language sometimes they have difficulties, because they must choose the right translation procedure and ensure that the meaning in source and target text is equivalent.  The aim of this article is to find the idiom’s equivalence in the source text (ST) and target text (TT), and to know what translation procedures used in idiom’s translation.  The Newmark’s translation procedure was used as theory in this article.  The analytical part is based on a Pramoedya Ananta Toer’s novel Rumah Kacaand its translation in German.  The author found 115 idioms in this novel, consist of 107 (93%) expression datas and 8 proverb datas (7%), then analyzed them based on Newmark’s translation procedures.  It was found that the most translation procedure used by the translator to translate expression is synonymy:  74 datas (64.4%), paraphrase:  18 datas (15.7%), cultural equivalent:  10 datas (8.7%), reduction:  3 datas (2.6%), and modulation:  2 datas (1.7%).  While to translate proverbs used three translation procedures, synonymy:  4 datas (3.5%), literal:  2 datas (1.7%), and paraphrase:  2 datas (1.7%).